2016
DOI: 10.1038/srep19027
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of deterministic domain wall trajectory in magnetic network structures

Abstract: Controlling the domain wall (DW) trajectory in magnetic network structures is crucial for spin-based device related applications. The understanding of DW dynamics in network structures is also important for study of fundamental properties like observation of magnetic monopoles at room temperature in artificial spin ice lattice. The trajectory of DW in magnetic network structures has been shown to be chirality dependent. However, the DW chirality periodically oscillates as it propagates a distance longer than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…However, care is needed because the walls may transform into domain walls of opposite chirality for particular magnetic fields and geometries 64,65 , and the propagation behaviour of the domain walls depends on the magnitude and orientation of the applied magnetic fields [66][67][68] . To circumvent these effects, the geometry of the Y-junctions can be modified so that the symmetry of the branches is reduced, giving a deterministic domain wall path that is independent of the domain-wall chirality 69 . It is also possible to nucleate domain walls in particular positions in connected artificial spin ice using a magnetic tip such as that found in a magnetic force microscope (MFM), thereby creating specific magnetic configurations at will 70 .…”
Section: Key Pointsmentioning
confidence: 99%
“…However, care is needed because the walls may transform into domain walls of opposite chirality for particular magnetic fields and geometries 64,65 , and the propagation behaviour of the domain walls depends on the magnitude and orientation of the applied magnetic fields [66][67][68] . To circumvent these effects, the geometry of the Y-junctions can be modified so that the symmetry of the branches is reduced, giving a deterministic domain wall path that is independent of the domain-wall chirality 69 . It is also possible to nucleate domain walls in particular positions in connected artificial spin ice using a magnetic tip such as that found in a magnetic force microscope (MFM), thereby creating specific magnetic configurations at will 70 .…”
Section: Key Pointsmentioning
confidence: 99%
“…Thus far, the poorly controlled nature of DW propagation through the cross without a syphon has been an effect that limits the use of n-CL structures for sensors. Despite some studies on the propagation of the DW in split paths [19,[22][23][24], DW dynamics propagating through the center of the cross is not yet fully understood, particularly its behavior about the reversal of the vertical arm of the cross.…”
Section: A Crossing Of Two Magnetic Stripesmentioning
confidence: 99%
“…Individual magnetic textures such as artificial skyrmions and merons can also be nucleated via domain imprinting in exchange coupled multilayers playing with geometry, in-plane and out-of-plane anisotropy layers or antiferromagnetic couplings [13][14][15][16][17][18][19]. In the case of magnetic nanostructures with in-plane magnetic anisotropy, magnetic vortices and edge half vortices are the most relevant topological defects needed to understand magnetization reversal [20] in nanowires [21] and bifurcations [22]. Also, in films with ordered arrays of antidots [23] or honeycomb lattices [24], it has been shown that vortex wall propagation can be controlled through the configuration of edge half vortices.…”
Section: Introductionmentioning
confidence: 99%